PENGEMBANGAN ALAT PRAKTIKUM FISIKA PADA TOPIK HUKUM KEKEKALAN MOMENTUM BERBASIS ARDUINO UNO MENGGUNAKAN SENSOR ULTRASONIK HC-SR94 - Ardianto, Ahmad; Suseno, Nyoto; Rosa, Friska Octavia; Prihandono, Eko (Universitas Muhammadiyah Metro, 2023)
Arduino uno/microcontroller can be applied in the world of education, one of which is used as material for the development of digital practicum tools. This research aims to; (1) develop a physics practicum tool in the mechanics course, namely the material for the law of conservation of momentum which is developed based on Arduino uno; (2) to find out how to design more precise practicum tools; (3) knowing the feasibility of the momentum conservation law practicum tool developed. This research is an ADDIE research which involves the stages of model development with five steps/development phases including: analysis, design, development or production, implementation and evaluation. Research data were collected using a validation questionnaire sheet, user response questionnaires and documentation. The results of this study are; (1) produce a product in the form of a physics practicum tool on the material of the law of conservation of momentum based on Arduino uno with an ultrasonic sensor HC-SR04; (2) the precision/precision of the practicum tool that has been developed has an accuracy value of 0.178 kg m/s; (3) the feasibility of the product of physics practicum tools on the material of the law of conservation of momentum based on Arduino uno with the ultrasonic sensor HC-SR04 as a whole is categorized as very feasible to use, namely getting a percentage value of 86% according to media experts, 91% according to material experts and 90% according to media experts. students/users and practicum tools developed are categorized as very suitable for use in practical activities. The product resulting from this research is a practical tool for the law of conservation of momentum based on Arduino uno using an ultrasonic sensor HC-SR04. In this development, it is not only practicum tools, the practicum tools developed are equipped with user manuals and practicum guides that function to make it easier for users to carry out practical activities.